Clinical Insights into RELA-Associated Disease: From Genotype to Phenotype and Exploring Treatment - Chun Pan; Cuifang Zheng; Yuhuan Wang; Jieru Shi; Lin Wang; Ying Huang (Genes, 2026)
Background/Objectives: RELA encodes the p65 subunit of NF-κB and plays a critical role in immune regulation, epithelial protection, and anti-apoptotic signaling. Pathogenic RELA variants cause monogenic immune dysregulation with heterogeneous clinical manifestations. However, genotype–phenotype relationships and optimal treatment strategies remain incompletely defined. Methods: We conducted a comprehensive literature-based analysis of reported individuals with RELA variants and additionally described a family carrying a RELA c.706C>T (p.R236*) variant, including a clinically affected proband and his variant-positive father with isolated vitiligo. Clinical, immunological, genetic, endoscopic, and therapeutic data were extracted and summarized using a module-based phenotypic framework. Exploratory analyses were performed to examine potential genotype–phenotype patterns and reported treatment responses. Results: A total of 72 individuals with RELA variants, including the proband and his variant-positive father from the present family, were analyzed. RELA-associated disease exhibited marked clinical heterogeneity, encompassing mucocutaneous, systemic inflammatory, autoimmune, gastrointestinal, hematologic, allergic/eosinophilic, and infection-related manifestations. Exploratory analyses suggested that truncating or splice-site variants were more frequently observed among individuals with mucocutaneous lesions, whereas missense variants appeared to be more common among those with autoimmune manifestations. Tumor necrosis factor (TNF) inhibitors were among the therapies associated with favorable reported responses. In the present family, the proband presented with early-onset Behçet-like intestinal inflammation and achieved clinical and endoscopic remission after thalidomide and dose-escalated infliximab treatment. Conclusions: This study expands the clinical spectrum of RELA-associated disease and highlights preliminary variant-related clinical patterns that require confirmation in larger independent cohorts. The available treatment experience suggests that TNF blockade may be considered as a therapeutic option in selected patients, although comparative efficacy cannot be established from the available data.